Frauen als Komponistinnen im Umfeld Mozarts: mit einem besonderen Augenmerk auf Maria Theresia Paradis - Korntner, Beate (Munich AVM Press, 2018)
Even if their names are almost forgotten, female composers made a significant contribution to cultural and musical life in Mozart's time. Maria Theresia Paradis, Marianne Martines, Josepha Auernhammer, Nanette Streicher, Franziska Lebrun-Danzi, Babette Ployer and Mozart's sister Nannerl are considered to be the most important representatives. Many of their works have not survived and the few that are known have been attributed to male composers for many years. Being a female musician and especially a female composer was difficult. It is no coincidence that Maria Theresia Paradis said: ‘Would my male colleagues in the arts forgive me if I dared to compete with them as a woman - even as a faceless woman?’ It was not easy to assert themselves and yet female composers were recognised by the public and could point to many successes. This book explores the question of the extent to which it was possible for a woman to hold her own alongside her male colleagues in Mozart's time. (Translated with Deepl.com)
Die Frau in 18. Jahrhundert -- Frauen als Komponistinnen im Unfeld W.A. Mozarts. Nannerl, als Schwester im Schatten des grossen Komponisten (1751-1829) ; Komponistionsschülerinnen von Mozart : die Tochter des Comte de Guines, Josepha Auernhammer und Babette Ployer (?) ; Komponieren als Zeitvertreb für Frauen in besonderen Berufe ; Nannette Streicher, née Stein, die Klavierbauerin (1769-1833) ; Franziska Danzi-Lebrun, die Sängerin (1756-1791) ; Komponieren als Beruf(ung) ; Josepha Auernhammer, Mozarts Schülerin (1758-1820) ; Marianna Martines (1744-1812) ; Maria Theresia Paradis (1759-1824), blinde Pianistin, Komponistin und Lehrerin -- Conclusio.
Includes bibliographical references (pages 71-75).
Keywords: Paradis, Maria Theresia von -- 1759-1824; Music history; Biography; Composer; Gender; Female; Austria